Stress Profile in Remotely Piloted Aircraft Crewmembers During 2 h Operating Mission - Valenzano, Anna; Moscatelli, Fiorenzo; Messina, Antonietta; Monda, Vincenzo; Orsitto, Raffaele; Zezza, Giovanna; Fiorentino, Giovanni; Salerno, Monica; Triggiani, Antonio I.; Viggiano, Andrea; Mollica, Maria P.; Carotenuto, Marco; et al. (Frontiers in Physiology, 2018)
Emotional stability is a key component for individual and team performance during both routine work and management of unexpected emergencies. Using a psycho-physiological approach operating the stress response was investigated in drone operators during operating conditions. Methods. Salivary-amylase (sAA), galvanic skin response (GSR) and anxiety were assessed over a 2-hours operating flight. Results. Compared to baseline values, operating GSR and sAA values increased in operating conditions. Moreover, these values were higher in Pilots than in Sensor Operators, indicating that their stress response was greater. These results were associated with an increase in anxiety level, highlighting a relationship between autonomic reactivity and anxiety component. Conclusions. This is the first report providing experimental evidences of the stress response related to Remotely Piloted Aircraft operations.